Penyuluhan Program Vaksinasi Booster Covid-19 Di Kabupaten Bengkayang - Novita, Wanda; Wahyudi, Raymond; Sebastian; Alip Hanoky (UNIB Press, 2023)
Corona virus began to run the world in 2019, and started to enter Indonesia in 2020. The government of Indonesia then implemented an alert status telated to public health, and made effort to increase people’s immunity through various ways, where one of which is by vaccination. However, there is a lot of Indonesian refuse to take the vaccine due to their believe, and the massive publication in media that sayas a lot of people die since they had vaccination. Institut Teknologi dan Bisnis Sabda Setia collaborate with Dinas Kesehatan, Pengendalian Penduduk, dan Keluarga Berencana socializing the benefits of vaccination, especially the third vaccination called booster to the community in Bengkayang regency. The socialization attended by 100 people from all over Bengkayang. At the end of the socialization, both parties agreed to sign a declaration of the willingness of all officials to carry out the third vaccine.